Pengembangan Potensi Olahraga Voli Di Rw 05: Upaya Pemberdayaan Masyarakat Oleh Kelompok 440 - Ratu Alsyafa, Melfianna; Jum’atia; Muhammad Rizki, Adam (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
Development of Volleyball Sports Potential in RW 05: Community Empowerment Efforts by Group 440 in KKN SISDAMAS highlights the importance of developing sports potential as a community empowerment strategy. Based on current literature, sports development can improve the quality of life of the community through improved health, education, and social awareness. In this context, the development of volleyball sports in RW 05 is a strategic effort to improve local residents’ physical and mental health. Group 440 in KKN SISDAMAS has carried out a series of activities included in the development of volleyball sports programs, such as basic training, local tournaments, and socialization about the benefits of sports for health. Current literature shows that sports programs can improve community health, increase social awareness, and strengthen community ties. For example, research conducted by Sunan Gunung Djati State Islamic University Bandung shows that KKN activities that focus on community empowerment can improve the quality of life of the community through various work programs that are relevant to the needs of the local community. In this case, the development of volleyball sports potential in RW 05 is a good example of community empowerment efforts carried out by Group 440 in KKN SISDAMAS. Thus, this article shows that sports development can be one of the effective strategies in improving the quality of life of the community and strengthening community ties.